The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00125-003-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the ACE (I/D) polymorphism on systemic and renal vascular responses to angiotensins in normotensive, normoalbuminuric Type 1 diabetes mellitus

Abstract: Aim/hypothesis. The renin-angiotensin-aldosterone system is important in diabetic nephropathy, with the angiotensin-converting-enzyme DD-genotype being a renal risk factor. The D-allele is associated with higher ACE concentrations, but functional consequences in diabetes mellitus are not known. To analyse these consequences, we assessed renal and systemic responsiveness to angiotensin I infusion, with the response to angiotensin II as reference. Methods. Uncomplicated Type 1 (insulin-dependent) diabetic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This is consistent with previous findings concerning kidney function and blood pressure in type 1 diabetic subjects selected on the basis of ACE genotype, studied during hyperglycemia (31), and during infusions of angiotensins 1 and 2 (32). During normoglycemia, ramipril had a dose-dependent effect on renal hemodynamics that did not differ with genotype.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous findings concerning kidney function and blood pressure in type 1 diabetic subjects selected on the basis of ACE genotype, studied during hyperglycemia (31), and during infusions of angiotensins 1 and 2 (32). During normoglycemia, ramipril had a dose-dependent effect on renal hemodynamics that did not differ with genotype.…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence to suggest that the reninangiotensin system is highly active during hyperglycemia in the renal circulation of subjects with type 1 diabetes (34,35). We and others (14,31,32) have demonstrated that these renal hemodynamic changes are greater in subjects carrying the ACE D allele than in those with the II genotype. Intraglomerular capillary hydraulic pressure, the main determinant of renal failure (36), is largely conditioned by interaction between the vasodilatory effects of nitric oxide (NO) and the vasoconstrictive effects of angiotensin 2.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…20,21 These findings strongly suggest that the enhanced progression of kidney function loss in DD and ID patients is the result of increased intrarenal activity of ACE. 5 In addition, the ACE/DD genotype has been shown to enhance the risk of developing diabetic glomerulopathy lesions in type 2 diabetic patients with microalbuminuria and macroalbuminuria. 22 In addition to nongenetic factors, drug responses are also known to be influenced by inherited factors (i.e., pharmacogenomics).…”
Section: Discussionmentioning
confidence: 99%
“…5 A meta-analysis of 14,727 type 1 and type 2 diabetic patients revealed an enhanced risk for development of diabetic nephropathy in the DD genotype compared with the II genotype. 6 Originally, Parving et al observed that the deletion allele of the ACE polymorphism reduces the long-term beneficial effect of ACE inhibition on the progression of overt diabetic nephropathy in patients with type 1 diabetes.…”
mentioning
confidence: 99%